Faktor-faktor yang berhubungan dengan tingkat kepuasan pasien rawat inap terhadap pelaksanaan konsultasi gizi ruangan di Rumah Sakit Umum Mataram - Siti Utami Sulasty; R Dwi Budiningsari; Setyowati Setyowati (Jurnal Gizi Klinik Indonesia, 2009)
Background:  Nutrition counseling is one of the nutrition services successful indicators in hospitals.  The quality of nutrition counseling will improve the effectiveness and efficiency of resources utility and furthermore, it will improve patients’ satisfaction.  The quality of nutrition counseling services effect directly on internal and external customers’ satisfaction. Evaluation about nutrition counseling services in hospital ward and its association with patients’ satisfaction was needed to determine priority aspects to be improved.Objective:  To determine factors that associate with the rate of hospitalized patients’ satisfaction towards nutrition counseling in Mataram Hospital.Method:  A total 38 hospitalized adult patients included in this observational study with cross sectional design. Proportional stratified sampling was conducted to determine subjects of study. Data collections included the description of nutrition counseling factors consisted of counselors, materials, methods, media, time, place, and visitation frequency of dietitians based on questionnaires completed directly by hospitalized adult patients. Spearman rank correlation and linear regression analysis were used to determine the association between nutrition counseling factors with the rate of hospitalized patients’ satisfaction, completely by multiple linear regressions to analyze all of nutrition counseling factors in the same time.Results: This study showed that counselors, time, place, and dietitians’ nutrition counseling visitation were the significant factors associated with the rate of hospitalized adult patients’ satisfaction (R = 0,086 p = 0,027; R = 0,099 p = 0,017; R = 0,108 p = 0,013; R = 0,166 p = 0,002, respectively).  The most dominant factors among all of associated factors were visitation frequency of dietitians (p = 0,035).Conclusion: There was a significant association between counselors, time, place, and dietitians’ nutrition counseling visitation frequency with the rate of hospitalized patients’ satisfaction.  The most dominant factors among all of associated factors were visitation frequency of dietitians.